2002
DOI: 10.1046/j.1529-8817.2002.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

HEAVY METAL‐INDUCED INHIBITION OF PHOTOSYNTHESIS: TARGETS OF IN VIVO HEAVY METAL CHLOROPHYLL FORMATION1

Abstract: The targets of heavy metal (here Cu2+ and Zn2+) attack on the photosynthetic apparatus of algae belonging to different phyla were investigated. Experiments with the green alga Scenedesmus quadricauda confirmed previous findings that according to the irradiance level two different phenomena occur, which were further characterized by specific changes in several photosynthetic parameters. The reaction occurring under low irradiance (shade reaction) is characterized by heavy metal substitution of Mg2+ in chl molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 53 publications
8
85
0
1
Order By: Relevance
“…There is increasing evidence to support the involvement of 14-3-3's in phosphorylation cascades involved in the response to reactive oxygen species (ROS) (Huber 2007). This may provide a connection between ROS generation resulting from copper inhibition of PSII and 14-3-3 induction (Kupper et al 2002;. Additional evidence from mammalian systems has linked various binding partners involved in apoptosis with 14-3-3 and comparative proteomic analysis has suggested that the partners and roles of 14-3-3's have been highly conserved among kingdoms (Paul et al 2009).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…There is increasing evidence to support the involvement of 14-3-3's in phosphorylation cascades involved in the response to reactive oxygen species (ROS) (Huber 2007). This may provide a connection between ROS generation resulting from copper inhibition of PSII and 14-3-3 induction (Kupper et al 2002;. Additional evidence from mammalian systems has linked various binding partners involved in apoptosis with 14-3-3 and comparative proteomic analysis has suggested that the partners and roles of 14-3-3's have been highly conserved among kingdoms (Paul et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Such chelation has been regarded as important for heavy metal resistance (see Kupper et al 2002). However, the synthesis of phlorotannins (brown algal polyphenolics) has been reported to be unaffected by copper exposure (Toth and Pavia 2000) so that alternate chelators may also be needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported earlier that metals such as cadmium, copper, and chromium ions directly inhibit PSII electron transport at the water-splitting system of the RC (Küpper et al 2002;Popovic et al 2003;Dewez et al 2005;Ait Ali et al 2006). …”
Section: Significance Of Photosynthetic-based Fluorescence Parametersmentioning
confidence: 93%